Investigating neoclassicism around Alexandre Tansman - Brandão, Luigi (Revista Vórtex, 2020)
In this essay, I investigate the issue of neoclassicism around the public figure of the polish composer Alexandre Tansman. The objective is to chart some of the ways in which the composer is related to neoclassicism. I begin by presenting an understanding of the term neoclassicism and proceed to an investigation of how commentators see Tansman's relation to it, both in relation to his ideas on music and art and in relation to compositional decisions and procedures. Toward the end of the essay, a section is dedicated to the issue of neoclassicism in Tansman's guitar works, in which I present an argument against the easy use of the term within this repertoire. The final section wraps up the discussion and presents a graphical representation of the results of the present investigation.